2014
DOI: 10.1007/s10853-014-8555-y
|View full text |Cite
|
Sign up to set email alerts
|

Reverse transformation of deformation-induced martensite in austenitic stainless steel studied by positron annihilation

Abstract: The reversion of deformation-induced a 0 -martensite in tension-deformed 1.4301 (EN) stainless steel was investigated using positron annihilation spectroscopy. The Doppler broadening of the annihilation line and positron lifetime spectroscopy were applied to study defect structure and its annealing behavior in samples with a similar deformation level but varying in a 0 -martensite amount. The difference in a 0 -martensite was obtained by applying different deformation temperatures, i.e., liquid nitrogen temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 62 publications
3
24
0
Order By: Relevance
“…After this stage, the S parameter values for the samples studied do not differ significantly. A similar behavior was observed for deformed 1.4301 SS and 1.4307 SS [12,16,17], but in that case, the decrease starts at higher temperature of about 200C and continues up to 450C, open triangles in Fig. 3.…”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…After this stage, the S parameter values for the samples studied do not differ significantly. A similar behavior was observed for deformed 1.4301 SS and 1.4307 SS [12,16,17], but in that case, the decrease starts at higher temperature of about 200C and continues up to 450C, open triangles in Fig. 3.…”
Section: Methodssupporting
confidence: 78%
“…The defect generation is less pronounced than during the -martensite reversion in stage II. The temperature range of stage III coincides with the increase in the S parameter for the deformed 1.4301 SS, which was ascribed to the generation of defects during -martensite reversion [12]. Volume contraction accompanying bcc or fcc change during -martensite reverse transformation results in volume excess that may contribute to the vacancy cluster formation.…”
Section: Methodsmentioning
confidence: 51%
See 1 more Smart Citation
“…The unchanged dislocation density is most probably caused by a balance between the annihilation of dislocations due to annealing and their formation owing to the stresses induced by the phase transformation. Earlier studies [32] showed that the phase transformation of α′-martensite to γ-austenite is accompanied by a volume contraction which may yield internal stresses and the formation of lattice defects. Indeed, it was revealed that vacancy clusters consisting of ~6-9 vacancies formed at the interface between α′-martensite and γ-austenite after the reverse phase transformation [32].…”
Section: Microstructure Evolution During Annealingmentioning
confidence: 99%
“…The deformation-induced martensite transformation into austenite is accompanied by migration and reduction of vacancies an creation of additional lattice imperfections [8]. The reverse process is then accompanied by the formation of annealing twins where the accumulated excessive energy is reduced [9].…”
Section: Resultsmentioning
confidence: 99%